1983
DOI: 10.1115/1.3266339
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection in Collector Cavities With an Isoflux Absorber Plate

Abstract: The boundary condition at the hot absorber plate in a solar collector will influence the natural convection in the enclosure. For the isoflux boundary condition and an isothermal cold wall an experimental and numerical study has been made for Ra numbers from 105 to 107 and inclinations from 20 to 90 deg with the horizontal. For vertical enclosures the heat transfer by natural convection was about 19 percent above that for an isothermal hot plate. This decreases with angle of inclination, to 9 percent at 20 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…From this important result it can be concluded that their results are also applicable to upward flow in meander type absorbers. For downward flow the heat loss was increased by more than 10 % compared to upward flow, which is in qualitative agreement with the results of both Hellström et al (1988) and Schinkel and Hoogendoorn (1983).…”
Section: Heat Transfer In Gaps With Non-isothermal Boundariessupporting
confidence: 92%
See 2 more Smart Citations
“…From this important result it can be concluded that their results are also applicable to upward flow in meander type absorbers. For downward flow the heat loss was increased by more than 10 % compared to upward flow, which is in qualitative agreement with the results of both Hellström et al (1988) and Schinkel and Hoogendoorn (1983).…”
Section: Heat Transfer In Gaps With Non-isothermal Boundariessupporting
confidence: 92%
“…In one experiment the strips were kept at the same temperature by individual heating. Because of the temperature stratification within the gap, the lowermost strip suffered a 5 times higher heat loss than the uppermost, which is in qualitative agreement with the numerical results of Schinkel and Hoogendoorn (1983).…”
Section: Heat Transfer In Gaps With Non-isothermal Boundariessupporting
confidence: 87%
See 1 more Smart Citation
“…The experimental setup consisted of two isothermal (cold and hot) plates of 0.2 • 0.3 m with variable distances. It has been described extensively in previous papers, Schinkel [15], [17] and [18]. Flow visualisation experiments and laser doppler anemometer measurements [17] were done to determine the effect of ~ on flow.…”
Section: Experimental Methodsmentioning
confidence: 99%